Active Ingredients from Aromatic and Medicinal Plants - El-Shemy, Hany A. (IntechOpen, 2017)
Recently, new compounds from medicinal plants were discovered, and they were used as anti-severe diseases. Therefore, this book covers interested research topics dealing with isolation, purification, and identification of active ingredients from wild and medicinal plants. This discovery will lead to an increase in the global pharmaceutical market as well as open such new gate for medicinal plant research. This book will add significant information to medical researchers and can be used for postgraduate students.